XMM–Newton observations of NGC 3268 in the Antlia Galaxy Cluster: characterization of a hidden group of galaxies at z ≈ 0.41. Issue 1 (28th May 2018) - Gargiulo, I D; García, F; Combi, J A; Caso, J P; Bassino, L P
ABSTRACT: We report on a detailed X-ray study of the extended emission of the intracluster medium (ICM) around NGC 3268 in the Antlia Cluster of galaxies, together with a characterization of an extended source in the field, namely a background cluster of galaxies at $z$ ≈ 0.41, which was previously accounted as an X-ray point source. The spectral properties of the extended emission of the gas present in Antlia were studied using data from the XMM–Newton satellite, complemented with optical images of Cerro Tololo Inter-American Observatory (CTIO) Blanco telescope, to attain for associations of the optical sources with the X-ray emission. The XMM–Newton observations show that the intracluster gas is concentrated in a region centred in one of the main galaxies of the cluster, NGC 3268. By means of a spatially resolved spectral analysis, we derived abundances of the ICM plasma. We found a wall-like feature in the north-east direction, where the gas is characterized by a lower temperature with respect to the rest of the ICM. Furthermore, using combined optical observations, we inferred the presence of an elliptical galaxy in the centre of the extended X-ray source considered as a background cluster, which favours this interpretation.